Evaluasi dan Strategi Pengembangan Bisnis “Wates Leather Goods” - Fauzan, Muhammad Dhafin Fauzan; Eka Tresna Gumelar; Rezi Muhammad Taufik Permana (Bandung Conference Series: Business and Management, 2023)
Abstract. "Wates Leather Goods" is one of the new players in the leather industry, founded in 2020. Since its inception, the company has successfully attracted consumers' attention with high-quality leather products that emphasize simple, functional, and minimalist designs. In the face of increasing competition in the market, "Wates Leather Goods" has realized the importance of improving business management and implementing effective business strategies to achieve sustainability and long-term growth. This report presents the results of the "Wates Leather Goods" business project aimed at enhancing business management through various analyses and business strategies such as Market and Competitor Analysis, SWOT Matrix, Space Matrix, Five Forces, and Balanced Scorecard. Business performance evaluation and financial metric measurements have also been conducted to measure the success of the business model implementation and identify areas that require improvement in the future. The evaluation results show company position in competitive quadran, significant improvement in finance with a reasonably good business performance, and successful achievements at the national and international levels. "Wates Leather Goods" focuses on product innovation and high-quality leather branding with simple and functional designs to meet customer needs. Through online expansion and strategic partnerships in the leather industry, the company increases brand visibility and adds value to its customers. Additionally, with sustainable business practices, "Wates Leather Goods" attracts environmentally and socially conscious consumers. It is expected that by implementing the recommendations from this report, "Wates Leather Goods" can continue to grow and achieve sustainable success in the leather industry. Abstrak. Perusahaan "Wates Leather Goods" adalah salah satu perusahaan baru di industri kulit, didirikan tahun 2020. Sejak awal pendiriannya, perusahaan ini telah berhasil menarik perhatian konsumen dengan produk-produk kulit berkualitas tinggi yang menonjolkan desain sederhana, fungsional, dan bergaya simple minimalist. Dalam menghadapi persaingan yang semakin ketat di pasar, "Wates Leather Goods" telah menyadari pentingnya meningkatkan pengelolaan bisnis dan mengimplementasikan strategi bisnis yang efektif untuk mencapai keberlanjutan dan pertumbuhan jangka panjang. Laporan ini menyajikan hasil dari proyek bisnis "Wates Leather Goods" yang bertujuan untuk meningkatkan pengelolaan bisnis melalui berbagai analisis dan strategi bisnis seperti Analisis Pasar dan Kompetitor, SWOT Matrix, Space Matrix, Five Forces, dan Balanced Score Card . Evaluasi kinerja bisnis dan pengukuran metrik keuangan juga telah dilakukan untuk mengukur keberhasilan implementasi model bisnis dan mengidentifikasi area yang memerlukan perbaikan di masa depan. Hasil evaluasi ini menunjukkan posisi perusahaan ada pada quadran competitive, adanya peningkatan yang cukup signifikan dalam aspek keuagan, performa bisnis yang cukup baik, serta berhasil meraih prestasi di tingkat nasional dan internasional. Adapun strategi pengembangan "Wates Leather Goods" fokus pada inovasi produk sebagai merek kulit berkualitas dengan desain sederhana dan fungsional untuk memenuhi kebutuhan pelanggan. Melalui ekspansi online dan kemitraan strategis dalam industri kulit, perusahaan meningkatkan visibilitas merek serta nilai tambah bagi pelanggan. Selain itu, dengan praktik sustainable business, "Wates Leather Goods" mampu menarik perhatian konsumen yang peduli pada dampak sosial dan lingkungan. Diharapkan dengan mengimplementasikan evaluasi dan strategi ini, "Wates Leather Goods" dapat terus berkembang dan mencapai keberhasilan yang berkelanjutan dalam industri kulit.